Standardising Patient Safety Related Outcomes in European ICUs: The SAFE‐ICU COST Action. - McEvoy, Natalie L.; Trapani, Josef; Latour, Jos M. (Nursing in Critical Care, 2026)
The article focuses on the SAFE-ICU COST Action (CA24107), a European Cooperation in Science and Technology programme launched in 2025 to improve patient safety in Intensive Care Units (ICUs) through standardized measurement of key patient safety outcomes such as pressure ulcers, healthcare-associated infections, and delirium. This four-year initiative involves over 250 clinicians, researchers, and educators from 42 countries, emphasizing inclusivity and early career researcher participation, particularly from less research-intensive regions. The programme aims to build interdisciplinary collaborations, harmonize measurement tools across European ICUs, assess current clinical practices, and promote education to reduce avoidable harms. By facilitating translation and cultural adaptation of assessment tools, SAFE-ICU seeks to enable consistent data collection and benchmarking, ultimately enhancing the quality of ICU care across diverse healthcare systems.